Boron-doped ruthenium dioxide hollow fiber catalyst as well as preparation method and application thereof
Through the preparation of boron-doped ruthenium dioxide hollow fiber catalyst, the problem of slow kinetics of water electrolysis OER and catalyst deactivation under acidic conditions is solved, and efficient and stable catalytic performance is achieved, which is suitable for proton exchange membrane electrolytic cells and electrolytic water.
Patent Information
- Application Number
- CN202411908853.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The prior art During water electrolysis under acidic conditions, especially the oxygen precipitation reaction (OER) kinetics are slow, and non-precious metal-based materials are prone to corrosion in a strong oxidation environment, resulting in catalyst deactivation.
Calcium alginate fibers were prepared by wet spinning with sodium alginate, and then crosslinked with boric acid and reacted with ruthenium trichloride. After pyrolysis treatment, boron-doped ruthenium dioxide hollow fibers were formed.
It realizes efficient catalytic OER and HER reactions in acidic electrolytes, with excellent catalytic activity and stability, and is suitable for proton exchange membrane electrolyte cells and electrolytic water catalysts.
Smart Images

Figure CN119710815A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalysts, and in particular to a boron-doped ruthenium dioxide hollow fiber catalyst, a preparation method and an application thereof. Background Art
[0002] Renewable energy-driven water electrolysis technologies, such as alkaline water electrolysis (AWE) and proton exchange membrane water electrolysis (PEMWE), provide promising pathways for hydrogen production. Notably, PEMWE has attracted extensive attention due to its fast reaction kinetics, high hydrogen purity, high current density, and good compatibility with renewable energy sources. However, the hydrogen production efficiency is limited by the sluggish kinetics of the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER), especially the latter. Non-precious metal (e.g., cobalt and nickel)-based materials can effectively accelerate the kinetics of water electrolysis in alkaline electrolytes; however, under acidic conditions, especially in the strongly oxidizing environment of the acidic OER, their structures are susceptible to corrosion, leading to catalytic deactivation.
[0003] Ruthenium (Ru) and iridium (Ir)-based oxides are widely considered as benchmark electrocatalysts for acidic OER. Among them, Ru-based electrocatalysts are superior to Ir-based electrocatalysts in terms of activity and price; however, they exhibit poor stability. The instability of Ru-based materials mainly originates from the over-oxidation of Ru species to form soluble RuO4 species. Introducing divalent and trivalent metals (such as Co, Zn, and Cr) into the RuO2 lattice is a widely adopted strategy to improve stability. This approach effectively alleviates the over-oxidation of Ru species by regulating the electron density to promote the formation of low-valent Ru. However, doped metals are prone to dissolution due to their thermodynamic instability. On the other hand, replacing Ru atoms with doped metal atoms will reduce the number of Ru-O structures, which is not conducive to further improving the activity. Non-metallic doping, such as Si, C, and B, can effectively alleviate the above problems.
[0004] The micro / nanostructure of the catalyst also plays a vital role in improving the catalytic performance of the electrocatalyst. For example, a one-dimensional structure with a large aspect ratio can accelerate the mass and electron transport during the reaction, while a hollow structure can expose more active sites and provide more contact area. In view of this, there is an urgent need for a one-dimensional hollow fiber acid electrocatalyst that provides efficient and stable catalysis for water electrolysis and proton exchange membrane electrolyzers. Summary of the invention
[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a boron-doped ruthenium dioxide hollow fiber catalyst and a preparation method and application thereof to solve the problems involved in the background technology.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a boron-doped ruthenium dioxide hollow fiber catalyst, which uses sodium alginate as a raw material, undergoes a wet spinning process to produce calcium alginate fibers, the calcium alginate fibers are mixed with a boric acid solution, rinsed and dried to obtain boric acid-crosslinked calcium alginate fibers, the boric acid-crosslinked calcium alginate fibers are fully mixed with a ruthenium trichloride solution, and dried to obtain a boric acid-crosslinked ruthenium alginate fiber precursor, which is then subjected to a pyrolysis treatment, the ruthenium ions are converted into ruthenium dioxide nanoparticles, the boric acid-crosslinked alginate fibers are converted into hollow fibers, and boron atoms are incorporated into the ruthenium dioxide lattice to form a boron-doped ruthenium dioxide oxygen evolution reaction electrocatalyst.
[0007] Preparation method of boron-doped ruthenium dioxide hollow fiber catalyst,
[0008] 1) Stirring the sodium alginate aqueous solution vigorously at room temperature, and filtering through a filter cloth to obtain a clear filtrate;
[0009] 2) the clarified filtrate is degassed in a spinning pot and then extruded through a viscose type spinneret into a coagulation bath containing an aqueous solution of calcium chloride to form nascent fibers;
[0010] 3) washing and stretching the as-spun fibers in distilled water, and then drying them to obtain calcium alginate fibers;
[0011] 4) Soaking the calcium alginate fibers in a boric acid solution for a certain period of time, then washing the obtained fibers in distilled water, and drying to obtain boric acid cross-linked calcium alginate fibers;
[0012] 5) adding the boric acid cross-linked calcium alginate fibers into a hydrochloric acid aqueous solution, ultrasonically immersing, and washing to obtain boric acid cross-linked hydrogen alginate fibers;
[0013] 6) adding the boric acid cross-linked hydrogen alginate fiber obtained in 5) into a mixed solution of ruthenium trichloride, water and ethanol, immersing the mixture in ultrasonic wave, rinsing and drying to obtain the boric acid cross-linked ruthenium alginate fiber;
[0014] 7) The boric acid cross-linked ruthenium alginate fiber is calcined in a tubular furnace through a carbonization process to obtain a boron-doped ruthenium dioxide hollow fiber.
[0015] Furthermore, the mass fraction of the sodium alginate aqueous solution is 1%, the mass fraction of the calcium chloride aqueous solution is 4%; and the mass fraction of the boric acid solution is 1%.
[0016] Furthermore, the concentration of the hydrochloric acid aqueous solution in (5) is 1 M, and the mass volume ratio of the boric acid cross-linked calcium alginate fiber to the hydrochloric acid aqueous solution is 1:100.
[0017] Furthermore, the mass ratio of the boric acid cross-linked calcium alginate fiber in 5) to the ruthenium trichloride in 6) is 20:1, the concentration of ruthenium trichloride in the mixed solution of water and ethanol is 0.5 mg / ml, and the volume ratio of water to ethanol is 3:2.
[0018] Furthermore, the calcination condition in 7) is to heat to 350° C. at a heating rate of 2° C. / min and maintain for 1 hour.
[0019] The invention discloses an application of a boron-doped ruthenium dioxide hollow fiber catalyst, and the application of the boron-doped ruthenium dioxide hollow fiber as an electrocatalyst in water electrolysis and proton exchange membrane electrolyzer.
[0020] Furthermore,
[0021] (1) Boron-doped ruthenium dioxide hollow fiber materials are used as anode and cathode catalyst materials to assemble a complete water splitting device;
[0022] (2) Boron-doped ruthenium dioxide hollow fiber material is used as the anode catalyst material and combined with Pt / C catalyst to assemble a proton exchange membrane electrolyzer.
[0023] Furthermore, the anode and cathode in (1) are both boron-doped ruthenium dioxide hollow fiber catalysts coated on 1 cm 2 On the Ti mesh, the catalyst loading was 1 mg.
[0024] Furthermore, the anode and cathode in (2) are 2 mg·cm -2 Boron-doped ruthenium dioxide hollow fiber catalyst and Pt / C catalyst were sprayed onto a polytetrafluoroethylene sheet with an active surface area of 4 cm 2 .
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention prepares calcium alginate fibers from sodium alginate through a wet spinning process, and then obtains boric acid cross-linked calcium alginate fibers through boric acid cross-linking. The preparation of boron-doped ruthenium dioxide hollow fibers is achieved by utilizing the characteristic that ruthenium ions can be complexed with boric acid cross-linked calcium alginate fibers. The boron-doped ruthenium dioxide hollow fibers can be used as proton exchange membrane electrolyzers and water electrolysis catalysts with excellent performance, and have high catalytic activity and good stability. The raw material sources are wide, and no expensive equipment is required, and a large amount of preparation can be carried out. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a SEM image of a boron-doped ruthenium dioxide hollow fiber according to an embodiment of the present invention;
[0028] Figure 2 is a TEM image of a boron-doped ruthenium dioxide hollow fiber according to an embodiment of the present invention;
[0029] Figure 3 is a HRTEM image of a boron-doped ruthenium dioxide hollow fiber according to an embodiment of the present invention;
[0030] Figure 4 This is an OER performance diagram of a boron-doped ruthenium dioxide hollow fiber in an acidic electrolyte according to an embodiment of the present invention;
[0031] Figure 5 This is a performance diagram of the OER stability of the boron-doped ruthenium dioxide hollow fiber in an acidic electrolyte according to an embodiment of the present invention;
[0032] Figure 6 This is a graph showing the HER performance of a boron-doped ruthenium dioxide hollow fiber in an acidic electrolyte according to an embodiment of the present invention;
[0033] Figure 7 This is a graph showing the electrolysis performance of the boron-doped ruthenium dioxide hollow fiber assembly according to an embodiment of the present invention;
[0034] Figure 8 This is a performance diagram of a PEM device assembled with a boron-doped ruthenium dioxide hollow fiber combined with Pt / C according to an embodiment of the present invention; DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] A boron-doped ruthenium dioxide hollow fiber catalyst is characterized in that: sodium alginate is used as a raw material, and a wet spinning process is performed to obtain calcium alginate fibers, the calcium alginate fibers are mixed with a boric acid solution, and then rinsed and dried to obtain boric acid-crosslinked calcium alginate fibers, the boric acid-crosslinked calcium alginate fibers are fully mixed with a ruthenium trichloride solution, and then dried to obtain a boric acid-crosslinked ruthenium alginate fiber precursor, which is then subjected to a pyrolysis treatment to convert ruthenium ions into ruthenium dioxide nanoparticles, the boric acid-crosslinked alginate fibers are converted into hollow fibers, and boron atoms are incorporated into the ruthenium dioxide lattice to form a boron-doped ruthenium dioxide oxygen evolution reaction electrocatalyst.
[0038] Preparation method of boron-doped ruthenium dioxide hollow fiber catalyst,
[0039] 1) A sodium alginate aqueous solution with a mass fraction of 1% and a calcium chloride aqueous solution with a mass fraction of 4% are prepared, and the sodium ions in the sodium alginate egg-box structure are exchanged with the calcium ions through a wet spinning process to obtain calcium alginate fibers.
[0040] 2) Calcium alginate fibers are mixed with 1% by mass of boric acid to obtain boric acid cross-linked calcium alginate fibers.
[0041] 3) 1 g of boric acid-crosslinked calcium alginate fiber was mixed with 100 mL of 1 M HCl and ultrasonically placed. During this process, hydrogen ions and calcium ions were exchanged to obtain boric acid-crosslinked hydrogen alginate fiber. The boric acid-crosslinked hydrogen alginate fiber was then mixed with 50 mg of ruthenium trichloride, 60 mL of water, and 40 mL of ethanol and ultrasonically placed. During this process, ruthenium ions and hydrogen ions were exchanged to obtain boric acid-crosslinked ruthenium alginate fiber.
[0042] 4) placing the boric acid cross-linked ruthenium alginate fiber in a tube furnace, heating it to 350° C. at a heating rate of 2° C. / min in an air atmosphere and maintaining it for 1 hour to obtain a boron-doped ruthenium dioxide hollow fiber.
[0043] Figure 1 is a SEM image of boron-doped ruthenium dioxide hollow fiber;
[0044] Figure 2 This is a TEM image of boron-doped ruthenium dioxide hollow fiber;
[0045] Figure 3 is the HRTEM image of boron-doped ruthenium dioxide hollow fiber;
[0046] Embodiment 2:
[0047] The invention discloses an application of a boron-doped ruthenium dioxide hollow fiber catalyst, and the application of the boron-doped ruthenium dioxide hollow fiber as an electrocatalyst in water electrolysis and proton exchange membrane electrolyzer.
[0048] (1) Boron-doped ruthenium dioxide hollow fiber materials are used as anode and cathode catalyst materials to assemble a complete water splitting device;
[0049] (2) Boron-doped ruthenium dioxide hollow fiber material is used as the anode catalyst material and combined with Pt / C catalyst to assemble a proton exchange membrane electrolyzer.
[0050] The anode and cathode in (1) are both boron-doped ruthenium dioxide hollow fiber catalysts coated on 1 cm 2 On the Ti mesh, the catalyst loading was 1 mg.
[0051] The anode and cathode in (2) are 2 mg·cm -2 Boron-doped ruthenium dioxide hollow fiber catalyst and Pt / C catalyst were sprayed onto a polytetrafluoroethylene sheet with an active surface area of 4 cm 2 .
[0052] Performance Test:
[0053] 1) The OER catalytic activity of the above products in 0.5M H2SO4 electrolyte was tested using an electrochemical workstation. The test results are as follows: Figure 4 As shown, in 0.5M H2SO4 electrolyte 10mA / cm 2 The overpotential at this current density is 220 mV, which is better than commercial RuO2.
[0054] like Figure 5 As shown, after 60 hours of testing in 0.5M H2SO4 electrolyte, its voltage remained basically unchanged, indicating excellent catalytic stability.
[0055] The HER catalytic activity was tested in 0.5M H2SO4 electrolyte. Figure 6 As mentioned above, in 0.5M H2SO4 electrolyte, an overpotential of 103mV is required to reach -10mA / cm 2 of current density.
[0056] 2) The boron-doped ruthenium dioxide hollow fiber material obtained above was used as the anode and cathode catalyst materials to assemble a complete water splitting device, and its performance was tested. Figure 7 It can be seen that the boron-doped ruthenium dioxide hollow fiber assembled full water splitting device obtained in this embodiment has an operating temperature of 50 mA / cm 2 The cell voltage at this current density was 1.54V.
[0057] The boron-doped ruthenium dioxide hollow fiber material obtained above was used as the anode catalyst material and combined with Pt / C catalyst to assemble a proton exchange membrane electrolyzer, and its performance was tested. Figure 8 As shown, only 1.76V is needed to reach 1A / cm 2 The current density is lower than that of commercial RuO2 (1.82V).
[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A boron-doped ruthenium dioxide hollow fiber catalyst, characterized in that: Sodium alginate is used as raw material and is wet-spinned to calcium alginate fibers. The calcium alginate fibers are mixed with a boric acid solution, rinsed and dried to obtain boric acid-crosslinked calcium alginate fibers. The boric acid-crosslinked calcium alginate fibers are fully mixed with a ruthenium chloride solution and dried to obtain a boric acid-crosslinked ruthenium alginate fiber precursor. After pyrolysis treatment, ruthenium ions are converted into ruthenium dioxide nanoparticles, and the boric acid-crosslinked alginate fibers are converted into hollow fibers. Boron atoms are incorporated into the ruthenium dioxide lattice to form a boron-doped ruthenium dioxide oxygen evolution reaction electrocatalyst.
2. The method for preparing the boron-doped ruthenium dioxide hollow fiber catalyst according to claim 1, characterized in that: 1) Stirring the sodium alginate aqueous solution vigorously at room temperature, and filtering through a filter cloth to obtain a clear filtrate; 2) the clarified filtrate is degassed in a spinning pot and then extruded through a viscose type spinneret into a coagulation bath containing an aqueous solution of calcium chloride to form nascent fibers; 3) washing and stretching the as-spun fibers in distilled water, and then drying them to obtain calcium alginate fibers; 4) Soaking the calcium alginate fibers in a boric acid solution for a certain period of time, then washing the obtained fibers in distilled water, and drying to obtain boric acid cross-linked calcium alginate fibers; 5) adding the boric acid cross-linked calcium alginate fibers into a hydrochloric acid aqueous solution, ultrasonically immersing, and washing to obtain boric acid cross-linked hydrogen alginate fibers; 6) adding the boric acid cross-linked hydrogen alginate fiber obtained in 5) into a mixed solution of ruthenium trichloride, water and ethanol, immersing the mixture in ultrasonic wave, rinsing and drying to obtain the boric acid cross-linked ruthenium alginate fiber; 7) The boric acid cross-linked ruthenium alginate fiber is calcined in a tubular furnace through a carbonization process to obtain a boron-doped ruthenium dioxide hollow fiber.
3. The method for preparing the boron-doped ruthenium dioxide hollow fiber catalyst according to claim 2, characterized in that: The mass fraction of the sodium alginate aqueous solution is 1%, the mass fraction of the calcium chloride aqueous solution is 4%; and the mass fraction of the boric acid solution is 1%.
4. The method for preparing the boron-doped ruthenium dioxide hollow fiber catalyst according to claim 2, characterized in that: The concentration of the hydrochloric acid aqueous solution in (5) is 1 M, and the mass volume ratio of the boric acid cross-linked calcium alginate fiber to the hydrochloric acid aqueous solution is 1:
100.
5. The method for preparing the boron-doped ruthenium dioxide hollow fiber catalyst according to claim 2, characterized in that: The mass ratio of the boric acid cross-linked calcium alginate fiber in 5) to the ruthenium trichloride in 6) is 20:1, the concentration of ruthenium trichloride in the mixed solution of water and ethanol is 0.5 mg / ml, and the volume ratio of water to ethanol is 3:
2.
6. The method for preparing the boron-doped ruthenium dioxide hollow fiber catalyst according to claim 2, characterized in that: The calcination conditions in 7) are heating to 350° C. at a heating rate of 2° C. / min and maintaining for 1 hour.
7. Use of the boron-doped ruthenium dioxide hollow fiber catalyst according to claim 1, wherein the catalyst is prepared according to the preparation method according to any one of claims 2 to 6, characterized in that: Boron-doped ruthenium dioxide hollow fibers as electrocatalysts for water electrolysis and proton exchange membrane electrolyzers.
8. The use of the boron-doped ruthenium dioxide hollow fiber catalyst according to claim 7, characterized in that: (1) Boron-doped ruthenium dioxide hollow fiber materials are used as anode and cathode catalyst materials to assemble a complete water splitting device; (2) Boron-doped ruthenium dioxide hollow fiber material is used as the anode catalyst material and combined with Pt / C catalyst to assemble a proton exchange membrane electrolyzer.
9. The use of the boron-doped ruthenium dioxide hollow fiber catalyst according to claim 8, characterized in that: The anode and cathode in (1) are both boron-doped ruthenium dioxide hollow fiber catalysts coated on 1 cm 2 On the Ti mesh, the catalyst loading was 1 mg.
10. The use of the boron-doped ruthenium dioxide hollow fiber catalyst according to claim 8, characterized in that: The anode and cathode in (2) are 2 mg·cm -2 Boron-doped ruthenium dioxide hollow fiber catalyst and Pt / C catalyst were sprayed onto a polytetrafluoroethylene sheet with an active surface area of 4 cm 2 .
Citation Information
Patent Citations
Manganese-doped ruthenium dioxide nanofiber material, preparation method and application of manganese-doped ruthenium dioxide nanofiber material in hydrogen evolution and oxygen evolution of alkaline electro-catalysis water
CN116573688A
Cerium-doped ruthenium dioxide electrocatalyst as well as preparation method and application thereof
CN117987865A
Lithium alginate fiber and preparation method thereof
CN118241475A
Iridium / ruthenium-based anode catalyst for water electrolysis, method for preparing same, and water electrolysis device using same
US20240263324A1
Cited By
Cobaltosic oxide loaded ruthenium dioxide fiber as well as preparation method and application thereof
CN120119281A
A ruthenium dioxide fiber supported on cobalt tetroxide, its preparation method and application
CN120119281B
Preparation method of heterogeneous metal and boron co-doped nano-porous ruthenium oxide catalyst
CN120591820A